The Anti-activator QslA Negatively Regulates Phenazine-1-Carboxylic Acid Biosynthesis by Interacting With the Quorum Sensing Regulator MvfR in the Rhizobacterium Pseudomonas aeruginosa Strain PA1201 - Fang, Yun-Ling; Chen, Bo; Zhou, Lian; Jin, Zi-Jing; Sun, Shuang; He, Ya-Wen (Frontiers in Microbiology, 2018)
Two almost identical gene clusters (phz1 and phz2) are responsible for phenazine-1-carboxylic acid (PCA) production in Pseudomonas aeruginosa strain MSH (derived from strain PA1201). Here, we showed that the anti-activator QslA negatively regulated PCA biosynthesis and phz1 expression in strain PA1201, but had little effect on phz2 expression. This downregulation was mediated by a 56-bp region within the 5’-untranslated region (5’-UTR) of the phz1 promoter, and was independent of LasR and RsaL signaling. QslA also negatively regulated Pseudomonas quinolone signal (PQS) production. Indeed, QslA controlled the PQS threshold concentration needed for PQS-dependent PCA biosynthesis. The QS regulator MvfR was required for the QslA-dependent inhibition of PCA production. We identified a direct protein–protein interaction between QslA and MvfR. The ligand binding domain of MvfR (residues 123–306) was involved in this interaction. Our results suggested that MvfR bound directly to the promoter of the phz1 cluster. QslA interaction with MvfR prevented the binding of MvfR to the phz1 promoter regions. Thus, this study depicted a new mechanism by which QslA controls PCA and PQS biosynthesis in P. aeruginosa.